An elite hockey player's experiences of video-based coaching: A poststructuralist reading. (February 2017) - Taylor, William G; Potrac, Paul; Nelson, Lee J; Jones, Luke; Groom, Ryan
In this article, we present a poststructuralist reading of Claire's (a pseudonym) experiences of receiving video-based coaching in elite level field hockey. Data were gathered through a series of in-depth interviews that formed part of a recursive and iterative data collection and analysis process. Interpreting Claire's stories through a neo-Foucauldian application of Mathiesen's synopticon revealed how the presence of a video camera mediated Claire's practice and imposed a critical gaze, one that became collectively and institutionally consumed. We argue that the thoughts presented in this paper have significant implications for coach practice and education and that, as a result, there is a need for further critical inquiry into coaches' uses of video-based technology.